Are social isolation and loneliness associated with cognitive decline in ageing? - Cardona, Margalida; Andrés, Pilar (Frontiers in Aging Neuroscience, 2023)
Objective. Social isolation and loneliness are associated with poor health (immunity, inflammation, etc.) in ageing. The purpose of this scoping review was to investigate the link between social isolation, loneliness (as distinct constructs, in contrast to previous published work) and cognition in cognitively healthy older adults. Method. We followed PRISMA-ScR guidelines. Our search, conducted between January 2017 and April 2021, yielded 2673 articles, of which, twelve longitudinal studies were finally identified as meeting the inclusion criteria. Multiple cognitive functions (short-term and episodic memory, attention and global cognitive functioning) were measured. The results showed that both social isolation and loneliness were associated with poor cognition in ageing, with depression as a possible mediator between loneliness and poor cognition. Some studies also suggested that the link between social isolation, loneliness and cognitive decline may be bidirectional. We conclude that both social isolation and loneliness may have a different impact on cognition. While depression may be an important mediator between loneliness and cognitive decline, the lack of cognitive stimulation may be a greater mediator between social isolation and cognitive health.